The implementation of an intensity regulated exercise programme in coronary artery bypass graft surgery patients: A pilot randomised controlled trial - Klopper, Margareet; Hanekom, Susan (SA Heart Journal, 2017)
AIM: To determine the safety and effect of an intensity regulated exercise programme, compared to a structured usual care mobilisation protocol, on the functional capacity of patients following coronary artery bypass graft (CABG) surgery, at discharge and 10 - 14 days after discharge. METHODS: Single centre, double-blinded, randomised controlled trial at a private hospital in Cape Town, South Africa. Subjects in the exercise group performed an intensity regulated exercise programme, while subjects in the control group were encouraged to mobilise out of bed. Both programmes were implemented within 24 hours after extubation following uncomplicated CABG surgery. Functional capacity was tested by means of the Six-Minute Walk Test (6MWT) at discharge and 10 - 14 days after discharge. RESULTS: Eligible patients (n=38) were randomly allocated to an exercise group (n=17) or a control group (n=21). The functional capacity of subjects in the exercise group was signifi cantly higher than that of the control group at hospital discharge, mean difference 103.10 meters (95%CI 23.39 - 182.81) (p=0.01). The exercise group did not further improve after hospital discharge (p=0.3) whereas the control group showed a signifi cant improvement (p<0.01) in walking distance over time. The mean difference in 6MWD at the second test was 44.89 meters (95%CI -84.33 - 174.10) (p=0.47). CONCLUSION: An intensity regulated exercise programme leads to higher levels of functional capacity on discharge and should be encouraged in the in-patient phase of cardiac rehabilitation following CABG surgery.